(untitled) (Damascus University Journal for legal sciences, 2025)
If the process of arriving at a specific and precise definition of the crime of aggression was difficult, the issue of the International Criminal Court’s jurisdiction over it was complex, given the powers possessed by the Security Council to determine the occurrence of an aggressive act based on the Charter of the United Nations, and the necessity for the International Criminal Court to adhere to this procedure as a matter that some found to be taking place. Within the framework of integration and interaction between the two bodies and their respect for the jurisdiction of the other, the first adjusts and decides and the second punishes and prosecutes, while others found it taking place within the framework of the court’s subordination to the Council within the framework of a set of legal rules that the court imposed on itself, and this study comes to present a legal study in light of the Charter The United Nations regarding the powers of the Security Council and its impact on the court’s jurisdiction to consider the crime of aggression.